An international expert consensus statement focusing on pre and post hair transplantation care - S. Vañó-Galván; C. N. Bisanga; P. Bouhanna; B. Farjo; V. Gambino; T. Meyer-González; T. Silyuk; Hair Transplant Surgery Expert Group (Taylor & Francis Group, 2023)
Aim To achieve international expert consensus and give recommendations on best practices in hair transplantation surgery, focusing on pre- and post-transplantation care. Methods A modified Delphi method was used to reach consensus. An international scientific committee developed an 81-statement questionnaire. A panel of 38 experts in hair transplantation from 17 countries across 4 continents assessed the questionnaire. Results Two consensus rounds were carried out, with 59 out of 81 statements (73%) reaching consensus. Expert recommendations emphasize the correct selection of candidates for hair transplantation and the need for patients to have received adequate medical treatment for alopecia before transplant. Comorbidities should be assessed and considered while planning surgery, and an individualized plan for perioperative care should be drawn up before transplant. Certain medications associated with increased risk of bleeding should be withdrawn before surgery. Specific recommendations for post-transplantation care are given. After transplantation, patients should gradually resume their normal haircare regimen. Close follow-up should be carried out during the first year after transplant. Conclusions This study presents numerous consensus-based recommendations on general aspects of hair transplantation, including candidate selection, medical therapy prior to transplantation, anesthesia, and resuming haircare after transplantation.